The practical reasoning of constitutional review (Universidad de San Andres Law Review, 2022)
Constitutionalists, when analyzing the constitutional review, usually assume a certain practical uniformity, that is, that whenever a court exercises such control, it is in fact carrying out the same activity. This paper sets out to partially challenge this assumption, demonstrating the diversity of forms in which the constitutional review is carried out in practice. Once this diversity is demonstrated, the paper will attempt to propose a way of conceptualizing control that makes explicit what its different variants have in common, using the notion of "legal defeasibility". The identification of the features common to the variants of control will make it possible to discuss which are the norms that regulate the exercise of the constitutional review and what is their scope. Finally, in the last section of the paper, it will be suggested how the control of constitutionality may come into tension with the ideal of the rule of law, thus questioning the widespread idea that the constitutional review and the rule of law are two sides of the same coin.